Composite Separators for Robust High Rate Lithium Ion Batteries. (1st June 2021) - Yuan, Botao; Wen, Kechun; Chen, Dongjiang; Liu, Yuanpeng; Dong, Yunfa; Feng, Chao; Han, Yupei; Han, Jiecai; Zhang, Yongqi; Xia, Chuan; (Xueliang) Sun, Andy; He, Weidong
Abstract: Lithium ion batteries (LIBs) are one of the most potential energy storage devices among various rechargeable batteries due to their high energy/power density, long cycle life, and low self‐discharge properties. However, current LIBs fail to meet the ever‐increasing safety and fast charge/discharge demands. As one of the main components in LIBs, separator is of paramount importance for safety and rate performance of LIBs. Among the various separators, composite separators have been widely investigated for improving their thermal stability, mechanical strength, electrolyte uptake, and ionic conductivity. Herein, the challenges and limitations of commercial separators for LIBs are reviewed, and a systematic overview of the state‐of‐the‐art research progress in composite separators is provided for safe and high rate LIBs. Various combination types of composite separators including blending, layer, core–shell, and grafting types are covered. In addition, models and simulations based on the various types of composite separators are discussed to comprehend the composite mechanism for robust performances. At the end, future directions and perspectives for further advances in composite separators are presented to boost safety and rate capacity of LIBs. Abstract : Composite separators for robust high rate lithium ion batteries (LIBs) are introduced with the state‐of‐the‐art preparation methods and recent research progress. The composite separators are classified into blending, layer, core–shell, and grafting structure types. Models and simulations are also discussed to comprehend the composite mechanism for robust performances of LIBs.